Barriers to Educator Implementation of a Classroom-Based Intervention for Preschoolers With Autism Spectrum Disorder - Wilson, Kaitlyn P.; Landa, Rebecca J. (Frontiers in Education, 2019)
There is considerable need for adoptable evidence-based interventions for implementation in public classrooms serving children with autism spectrum disorders (ASD) during the preschool years, an important period in neurodevelopment. Barriers to implementation, including gaps in teacher education, contribute to the research-to-practice gap and may compromise child outcomes. This qualitative study collected feedback from educators and administrators during their participation in the iterative development phase of a larger project to translate and preliminarily trial an evidence-based intervention in public preschool classrooms. Barriers were identified in areas of educator preparedness, engagement, and cohesion, complexity of instructing students with ASD, limited time/resources, and administrator support. Educators and administrators differed in their perspectives. Innovative strategies are presented for enhancing transportability, along with discussion of implications for teacher education practices and related policy.